Observations on the chlamydospore germination of Entyloma vignae, the causal agent de cowpea smut - Prabhu, Anne Sitarama; Albuquerque, Fernando Carneiro (Pesquisa Agropecuaria Brasileira, 2014)
The chlamydospores of Entyloma vignae Batista, Bezerra, Ponte and Vasconcelos, collected from the infected leaves of cowpea (Vigna unguiculata (L.) Walp.) were germinated and produced nonseptate promycelia of variable length. The promycelium was characterized by branching at the distal end bearing clusters of 10 to 20 primary sporidia. The adjacent compatible primary sporidia exhibited fusion in pairs forming typical H - shaped structures. The secondary infective mycelium inducing leaf lesions had originated from the fused primary sporidia. The mycelium in the culture produced clusters of chlamydospores which were nonpathogenic.